Academic digital literacy training to improbe student's academic success. - Anwar, Zainul; Balqis Candra Kirana, Diva (SHS Web of Conferences, 2025)
The development of information technology requires students to have good academic digital literacy skills to support their study success. However, many students still have difficulty in accessing, evaluating, and utilizing academic information sources effectively. This study aims to evaluate the effectiveness of academic digital literacy training in improving students' academic success, as measured by increasing digital literacy, academic assignment grades, and perceptions of academic success. The study used a quasi-experimental design (one group pretest-posttest design) involving 60 students from social science and education study programs. The training was conducted in six sessions covering scientific information searches, use of reference management, citation writing, and academic ethics. The instruments used included academic digital literacy tests, final assignment grades, and a scale of perceptions of academic success. Data analysis was carried out using a paired sample t-test. The results showed a significant increase in academic digital literacy scores (mean pretest = 62.13; posttest = 83.45; p < 0.001), final assignment grades (mean pretest = 75.62; posttest = 84.73; p < 0.001), and students' perceptions of academic success (mean pretest = 3.32; posttest = 4.18; p < 0.001). Academic digital literacy training has been shown to be effective in improving students' digital literacy skills and academic success.